Análisis de algunos procesos en el sistema de selección de beneficiarios (SISBEN) y satisfacción en la prestación del servicio de salud, municipio de Rionegro, Antioquia, 1998 (2000)
ABSTRACT: The Health General System of Social Security is a mixed organization constituted by two regimens, the contributive and the one subsidized, they will have a national coordination and financial channels of solidarity. In this article some aspects of the focalization, affiliation and satisfaction of the users who are the object of the subsidy are analyzed in the municipality of Rionegro (Antioquia) in the year of 1998. The results allow to conclude that the population with regard to the public services is quite benefited by the municipal policies, since the lowest percentage of public services is the toilet connected to the sewer system (78%), with an interval of trust of 95% of 73.94 to 82.95 which is considerably high. Regarding the holding of the house it was found that 42% of the population subsidized rents houses, 24% has another housing way, being reflected the unprotected conditions of the tendency of improvement, since only 11.25% diminished these conditions. A moderated and positive tendency was found (0.27) between socioeconomic stratum and SISBEN level.